IoT in Special Education - Moraiti, Ioanna; Fotoglou, Anestis; Dona, Katerina; Katsimperi, Alexandra; Tsionakas, Konstantinos; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
In recent years, there has been an increase in new technologies and their effects in many sectors of life. The importance of IoT in special education and training acquires more and more value over time. Collaboration between technology and educational specialties involved in the educational teaching of individuals is the key to students’ holistic evolution and development. The purpose of this article is to highlight the impact of IoT on the education and health promotion of students in special schools as well as children and adolescents with motor and mental disabilities. The techniques and approaches as a product of therapies and teachings have as their main axis the rehabilitation and functionality of the students and as a consequence of them the most complete awareness and cultivation of their positive emotions with the completion of the IoT intervention programs with the help of sensors that exist in smart devices. The findings highlighted through this article revealed cases of children and adolescents with special needs who benefited from the IoT programs to be reported. The following applications and their analysis led to the conclusion that the dynamic presence of these special interventions in various forms can be administered and improve the functionality & mental health of people with educational needs, a result that was expected by the research team making this research effort.